FRI0092 Lung Disease among Rheumatoid Arthritis Patients – Results from Ontario BIOLOGICS Research Initiative (OBRI). (10th June 2014) - Mittoo, S.; Jacob, B.; Bombardier, C.
Abstract : Background: Lung disease (LD) is a major, extra-articular complication and co-morbid condition among patients with rheumatoid arthritis (RA). Many disease-modifying agents (DMARDs) have safety concerns when used in the treatment of RA patients with chronic lung disease. Objectives: To describe the clinical characteristics of RA patients with LD in a population-based cohort and compare patterns of DMARD use at baseline among patients with and without LD. We also sought to evaluate the difference in clinical outcomes of RA patients with and without LD at 1-year follow-up. Methods: Patients with RA were recruited from the Ontario Best Practice Research Initiative (OBRI), a clinical registry of early and established RA patients followed in routine care. This is an analysis of a prospective cohort of adult patients with a physician-diagnosis of RA who had at least 1 swollen joint. Lung disease was defined as the presence of interstitial lung disease (ILD), pulmonary embolism (PE), chronic obstructive airway disease (COPD), asthma, and other lung disorders. Patients without LD were considered those who did not have LD at baseline or at their last follow-up study visit. Clinical characteristics between RA patients with and without LD were compared using t-test and chi-squared. Results: Among 2, 328 patients, 286 (12%) had LD and 1802 (86%) did not. Of those with LD, 123 (43%) had asthma, 64 (22%) had COPD, 53 (19%) had ILD, and 8 (3%) had PE and/or other LD. At baseline, RA patients with LD were significantly older in age (62.3±11.9) years compared to those without LD (56.3±12.8 years) (p≤0.001). Majority (78%) were female with a mean disease duration of 8.6 years. LD patients had higher ESR and CRP values at baseline, but tender and swollen joint counts did not significantly differ. LD patients were more frequently treated with BIOLOGICS (9.9% vs 5.1%, p<0.05), but received less methotrexate (50.4% vs 59.0%, p<0.05) compared to non-LD patients. At 1-year follow-up, RA patients with LD compared to those without LD had significantly greater number of tender joints (mean ± SD of 4.0±6.1 and 2.7±4.4, p=0.03), higher ESR (26.1±21.4), greater DAS28 scores (p=0.04), and higher levels of HAQ (p=0.02). Conclusions: Despite same disease activity at baseline, lung disease patients had higher DAS28 scores compared to without lung disease at 12 months. The factors that contribute to discrepancy and the reasons for the worse disease activity needs to be explored further. Acknowledgements: OBRI Investigators Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.5713